REVIEW: PENGEMBANGAN PAPAN PARTIKEL DENGAN FILLER DARI BERBAGAI MACAM RESIDU PERTANIAN - Miranti Maya Sylvani (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Wood is still an important forest commodity in Indonesia because wood is a resource that is widely used for various uses, although it is classified as a resource that can be simplified, its potential continues to decrease due to increasing needs. Agricultural residues and wood waste can potentially be used in a number of ways. Based on its designation, wood waste can be sorted, processed and provided as a raw material for making particle boards. Particleboard is made from particles of wood or other fibrous material, which are shaped and pressed together using an organic binder together with one or more materials, such as heat, pressure, catalyst, and so on. A good selection of agricultural residues including wheat straw, sugarcane, sunflower seed husks, bamboo and palm have been used successfully in the manufacture of particleboard. On particle board, the commonly used binders are urea formaldehyde, and phenol formaldehyde.